Respiratory monitoring during neonatal resuscitation using a supraglottic airway device vs. a face mask. (February 2022) - Pejovic, Nicolas J.; Cavallin, Francesco; Mpamize, Allan; Lubulwa, Clare; Höök, Susanna Myrnerts; Byamugisha, Josaphat; Nankunda, Jolly; Tylleskär, Thorkild; Trevisanuto, Daniele
Abstract: Objective: To evaluate the respiratory function of asphyxiated infants resuscitated with i-gel supraglottic airway (SGA) vs. face mask (FM) in a low-resource setting. Methods: In this sub-study from the NeoSupra trial, respiratory function during the first 60 inflations was evaluated in 46 neonates (23 with SGA and 23 with FM) at the Mulago National Referral Hospital, Uganda. The primary outcome was the mask leak (%). The secondary outcomes included inspired (VTi) and expired (VTe) tidal volumes, and heart rate response to ventilation. Results: Median mask leak was 40% (IQR 22–52) with SGA and 39% (IQR 26–62) with FM (p = 0.38). Median VTe was 7.8 ml/kg (IQR 5.6–10.2) with SGA and 7.3 ml/kg (IQR 4.8–11.9) with FM (p = 0.84), while median VTi was 15.4 ml/kg (IQR 11–4-17.6) with SGA and 15.9 ml/kg (IQR 9.0–22.6) with FM (p = 0.68). A shorter time was needed to achieve heart rate > 100 bpm in SGA (median 13 s IQR 9–15) with respect to FM arm (median 61, IQR 33–140) (p = 0.0002). Conclusion: Respiratory function was not statistically different between neonates resuscitated with SGA vs. FM. SGA was associated with faster heart rate recovery compared to FM in the subgroup of neonates with bradycardia. Further research is needed to investigate possible advantages of SGA on respiratory function at birth.